Sheikh Nawawi Al-Jawi’s Sufism Thoughts Of The Book Marăqil ‘Ubūdyah - Subaidi; Untung, Slamet; Marpuah, Siti; Embong, Rahimah; Ramlan , Siti Rosilawati (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2023)
The purpose of this study is to explain the sufism thoughts of Sheikh Nawawi al-Jawi in the book marăqil 'ubūdiyah. This type of research is library research. The uniqueness of his sufism thought is related to three fundamental things, namely: first, a sălik when he first enters the world of tasawuf he must strengthen his shari'ah teachings, because according to sheikh Nawai shari'a are some of God's laws ordered by the Messenger to mankind originating from God in the form of obligatory laws, sunnah, haram, makruh and mubah; second, sălik carry out various obligations, traditions, leave various prohibitions, stay away from excessive things that are permissible, carry out caution such as: wara', riyadhah in the form of literacy, hunger and silence; third, understanding the essence of everything, such as witnessing Allah's names (names), Allah's attributes, witnessing the Essence and secrets of the Qur'an, the secrets of prohibition, permissibility, and some unseen knowledge that cannot be obtained from a person. teacher, but the knowledge is understood from God. In the end, it is hoped that this article will provide readers with a deeper understanding of Sheikh Nawawi sl-Jawi's taswuf thoughts which combine sharia, tariqat and the essence of Islam.